Managers’ Entrenchment, Governance and Bank Performance - Mselmi, Aymen; Regaieg, Boutheina (International Journal of Economics and Financial Issues, 2017)
This paper examines the relationship between managers’ entrenchment, governance and financial and stock market performance of Tunisian banking institutions listed on the Tunis Stock Exchange (TSE). We first propose to model the level of managers’ theoretical entrenchment. Second, we examine a panel data to determine the relationship between the different internal banking governance mechanisms, including managers’ entrenchment, on banking performance. To this end, our study examines a sample of 11 Tunisian banks over a period stretching from the first half of 2006 to the second half of 2013.The results indicate that "good" governance practice codes of banking institutions often represent poor performance. On the other hand, managers’ theoretical entrenchment contributes to improving the financial performance of Tunisian banking institutions. Keywords: banking governance; managers’ entrenchment; market performance; JEL Classifications: G01, G20, G30